2011
DOI: 10.1590/s0100-29452011000300040
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização biométrica, física e química de frutos da palmeira bocaiuva Acrocomia aculeata (Jacq) Lodd

Abstract: Frutos de palmeira bocaiuva (Acrocomia aculeata (Jacq.) Lodd.), coletados em Dourados (MS) e Presidente Epitácio (SP), foram analisados quanto ao aspecto biométrico, a composição química e as características físicas, visando a avaliar seu potencial alimentício. Os frutos de bocaiuva das regiões de procedência não apresentaram diferenças significativas entre si nas características biométricas. O rendimento médio da polpa foi de 42% em relação ao fruto inteiro, sendo superior ao encontrado na literatura para out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 11 publications
0
4
0
11
Order By: Relevance
“…Another edible palm fruit from the Arecaceae family is the macaúba or coyol (Acrocomia aculeata Mart), widely distributed in Brazil, especially in the Cerrado region (Sanjinez-argandoña & Chuba, 2011). Silva et al (2008) reported lower moisture (34.32 g/100 g) and higher fiber (11.14 g/100 g) contents for the macaúba from the Cerrado in Goiás state, when compared to buritis from both regions analyzed; however, the contents of protein (2.76 g/100 g) and lipids (14.93 g/100 g) were similar.…”
Section: Composition In Nutrients and Caloric Valuementioning
confidence: 99%
“…Another edible palm fruit from the Arecaceae family is the macaúba or coyol (Acrocomia aculeata Mart), widely distributed in Brazil, especially in the Cerrado region (Sanjinez-argandoña & Chuba, 2011). Silva et al (2008) reported lower moisture (34.32 g/100 g) and higher fiber (11.14 g/100 g) contents for the macaúba from the Cerrado in Goiás state, when compared to buritis from both regions analyzed; however, the contents of protein (2.76 g/100 g) and lipids (14.93 g/100 g) were similar.…”
Section: Composition In Nutrients and Caloric Valuementioning
confidence: 99%
“…Outros, com enfoque mais específico em espécies de interesse comercial, abordaram características da semente sob o aspecto morfoanatômico (Araújo et al 2000;Aguiar & Mendonça 2003;Panza et al 2004;Mendonça et al 2008;Nazário et al 2013) e biométrico Reis et al 2010;Sanjinez-Argandoña & Chuba 2011). Contudo, mais pesquisas a respeito das estruturas reprodutivas desse grupo de plantas são necessárias para contribuir com programas de conservação dos ecossistemas e manutenção dos recursos naturais amazônicos (Mendonça et al 2008).…”
Section: B a C T R I S M A R A J A M A R T C O N H E C I D Aunclassified
“…Além disso, pode auxiliar na compreensão da variabilidade genética das espécies, relacionada a fatores ambientais, principalmente quando estas possuem ampla distribuição geográfica e adaptação a diversos ambientes (Sanjinez-Argandoña & Chuba 2011).…”
Section: B a C T R I S M A R A J A M A R T C O N H E C I D Aunclassified
“…Several chemical compounds with high antioxidant potential have already been described in A. aculeata. The fruit pulp is known to contain oleic acid [26], β-carotene [27], and α-tocoferol, whereas the kernel has lauric and oleic acids [28]. Although fruits are more widely used and studied, the leaves are used in animal nutrition [29] and no toxicity has been reported [30].…”
Section: Introductionmentioning
confidence: 99%